Awareness of Social Engineering Attacks and their Relation to the Ability to Persuade among users of Social Networking Sites - Turki, M, Alotayan, (Journal of Ecohumanism, 2024)
Aimed Education Current into Detection levels Awareness of social engineering attacks(ASEA) and their relationship to the ability to persuade users of social networking sites, and recognize the differences in In the level of awareness of social engineering attacks And the ability to persuade among social media users according to variables of age, place of residence, economic level, educational level, and the degree to which awareness of social engineering attacks affects the ability to mask by revealing the affective relationship between variables. The study sample consisted of (415) responding to the study tools. To achieve the objectives of the study, the social engineering scale was used by Vrhovec (2021). And the measure of persuasion ability by Busch et al. (2013. The results demonstrated that social media users' awareness of social engineering attacks and their ability to persuade were around average, with an overall scale average of 3.23 and an overall persuasion ability measure of 3.34. A correlation coefficient of 0.418 at the statistical significance level (α = 0.05) showed that there was a positive and statistically significant relationship between the participants' perceptions of their awareness of social engineering attacks and their ability to persuade on social networking sites. The results of the study also showed a statistically significant effect at the level of significance (α≤0.05) for the impact of awareness of social engineering attacks on the ability to persuade from the point of view of the study sample, as the correlation coefficient (R) (418), while the coefficient of determination (R2) indicates that awareness of social engineering attacks (as an independent variable) explains (17.5%) of the variation in the variable (ability to persuade) (as a dependent variable), and the rest of the percentage means that there are other independent variables that are not mentioned in The study model - or may be due to random error, and the results of the study indicated that there are no differences in the ability to persuade users of social networking sites according to variables, place of residence, economic level, educational level, as shown in the table that there are differences according to the two age variables, where it was found that there are differences between the category of 18-20 and the category of 24 and above and in favor of the category of 18-20 on the ability to convince totally. Regardless of demographic variables such age, place of residence, socioeconomic level, or level of education, the study found that knowledge of human engineering assaults was constant.